Complete Response to Nivolumab in Recurrent/Metastatic HPV-Positive Head and Neck Squamous Cell Carcinoma Patient After Progressive Multifocal Leukoencephalopathy: A Case Report - Locati, Laura Deborah; Serafini, Mara Serena; Carenzo, Andrea; Canevari, Silvana; Perrone, Federica; Orlandi, Ester; Delbue, Serena; Cavalieri, Stefano; Berzeri, Giulia; Pichiecchio, Anna; Licitra, Lisa Francesca; Marchioni, Enrico; et al. (Frontiers in Oncology, 2022)
In an immune-competent context nivolumab showed long-term benefit in overall survival in recurrent/metastatic head and neck squamous cell carcinoma (HNSCC); however, in special cancer population such as these patients with immunodeficiency and viral infections, data on checkpoint inhibitors (ICI) activity are scant. Herein, we report a patient with a Human papilloma virus (HPV)-related oropharyngeal cancer (OPC) and CD4 lymphocytopenia. After a first-line treatment complete remission, the patient experienced Human Polyomavirus (JCV) infection in the brain. Consequently, to the recovery from progressive multifocal leukoencephalopathy (PML) the patients metastasized and was enrolled in a single-arm trial with nivolumab (EudraCT number: 2017-000562-30). A complete and durable response (more 3 years) was observed after 10 nivolumab injections Q2wks, interrupted for persistent drug related G2 diarrhea and a syndrome of inappropriate antidiuretic hormone secretion. We describe the circulating immune profile (before-, during- and after nivolumab), consistent with the clinical history. Moreover, during nivolumab treatment, brain MRI evidenced the presence of small punctuate areas of contrast enhancement, reflecting a mild immune response in perivascular spaces. By cytofluorimetry, we observed that during JCV infection the patient’s CD4/CD8 ratio was under the normal values. After JCV infection recovery and before nivolumab treatment, CD4/CD8 ratio reached the normality threshold, even if the CD4+ T-cell count remained largely under the normal values. During ICI, gene expression xCell analyses of patient’s circulating immune cells, showed a progressive normalization of the total immune profile, with significant boost in CD4+ and CD8+ T-cells and a reduction in NK T, comparable to the circulating immune profile of reference tumor-free HNSCC patients. The present case supports the activity of ICI in special cancer patients’ populations; whether JCV and HPV infections (alone or together) might have a possible role as immune booster(s), require further investigations.